الانعكاسات المالية والتجارية للرسوم الكمركية في الاقتصاد العراقي (1995- 2010) (المجلة العراقية للعلوم الاقتصادية, 2018)
Customs duties is one of the instrument used by the countries to achieve a number of aims. But the nature of the Iraqi economy and the difficult conditions led to back of its importance as a source of income, in addition to its importance in the protection of the local production, And ineffectiveness in economic changes. So the study tried to declaration the roles that can be played by the customs tariff to variety of the Iraqi economy, according to its advantage to faces the problem of the clearing another types of incomes.